Effect of 532 nm Nd:YAG laser irradiation on the optical properties of Ge1Se2.5 glass film. Issue 16 (20th September 2021) - Deepika,; Dixit, M.; Kundu, K.; Singh, Hukum
Abstract : Ge1 Se2 .5 alloy was prepared using the melt quenching method and the film was deposited by the thermal evaporation method. The as-prepared film was irradiated with Nd:YAG laser at 532 nm wavelength for different durations. The structural and morphological characterization indicates that the film has nanoparticles of different shapes with sizes varying from 80 to 300 nm and the structure becomes more crystalline on laser irradiation. The refractive index of the film increases, while the band gap decreases on laser irradiation. The dispersion behaviour of refractive index was studied using the WDD model. The decrease in band gap is attributed to the increase of laser-induced defects, which consequently narrows the energy gap. The non-linear optical parameters were found to increase with an increase in laser irradiation time. The increase in these parameters and transformation from the amorphous to the polycrystalline phase make laser-irradiated films suitable for non-linear optical devices and optical recording media.